An intuitive approach to innovate a low cost Braille embosser. (2018) - Chowdhury, Dhiman; Haider, Mohammad Zakaria; Sarkar, Mrinmoy; Refat, Mustakim; Datta, Kanak; Fattah, Shaikh Anowarul
Braille printers are the most convenient way to emboss the texts on a Braille paper. But existing embossers are multiple times more expensive than the normal printers. In this paper, an innovative design of a low cost Braille printer is presented. The design being not dependent on expensive tools is an efficient solution. In the proposed Braille system, major concentration is given to develop the actuators which emboss the impressions on the Braille paper to make dots to decode text language in Braille format. Unlike conventional mechanisms, gear DC motors are utilised to design efficient and inexpensive actuators. Additionally, the overall printing system involves cost efficiently designed inter-dependent components, such as customised printing software, wireless communication system, sensing mechanisms, and compact mechanical setup. Extensive testing under different conditions is carried out and it is found that the proposed design can provide satisfactory embossing performance at a very low cost.